2022
DOI: 10.3390/vaccines10060961
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines and Autoimmune Hematologic Disorders

Abstract: Worldwide vaccination against SARS-CoV-2 has allowed the detection of hematologic autoimmune complications. Adverse events (AEs) of this nature had been previously observed in association with other vaccines. The underlying mechanisms are not totally understood, although mimicry between viral and self-antigens plays a relevant role. It is important to remark that, although the incidence of these AEs is extremely low, their evolution may lead to life-threatening scenarios if treatment is not readily initiated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 113 publications
0
30
1
Order By: Relevance
“…Altered hematopoiesis might have contributed to neutropenia. Severe aplastic anemia (affecting the hematopoietic stem cells and characterized by neutropenia and thrombocytopenia)-, cytopenia-and thrombocytopenia cases have all been reported with this platform in humans [43][44][45][46][47][48][49]. One small human study (56 volunteers) that monitored the immunological changes induced by this vaccine up to 21 days after the second shot reported a significant fluctuation in white blood cell numbers after the second injection of mRNA-LNP [11].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Altered hematopoiesis might have contributed to neutropenia. Severe aplastic anemia (affecting the hematopoietic stem cells and characterized by neutropenia and thrombocytopenia)-, cytopenia-and thrombocytopenia cases have all been reported with this platform in humans [43][44][45][46][47][48][49]. One small human study (56 volunteers) that monitored the immunological changes induced by this vaccine up to 21 days after the second shot reported a significant fluctuation in white blood cell numbers after the second injection of mRNA-LNP [11].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…According to the statistical data from the TFDA website (https://www.cdc.gov.tw/En/File/Get/YTqTkmtAHH7fmK Y6JF3l_A), 93. phenomena, including vaccine-induced immune thrombotic thrombocytopenia, immune thrombocytopenic purpura, and rheumatoid arthritis, could be associated with COVID-19 vaccines (52)(53)(54)(55). Several studies have reported that SARS-CoV-2 infection could induce the production of autoantibodies (33,34,56).…”
Section: Discussionmentioning
confidence: 99%
“…Severe aplastic anemia (affecting the hematopoietic stem cells and characterized by neutropenia and thrombocytopenia)-, cytopenia-and thrombocytopenia cases have all been reported with this platform in humans [43][44][45][46][47][48][49]. One small human study (56 volunteers) that monitored the immunological changes induced by this vaccine up to 21 days of the second shot reported a significant fluctuation in white blood cell numbers after the second injection of mRNA-LNP [11].…”
Section: Discussionmentioning
confidence: 99%